Progress in the treatment of Parkinson-Plus syndromes. (February 2019) - Olfati, Nahid; Shoeibi, Ali; Litvan, Irene
Abstract: Progressive supranuclear palsy (PSP), corticobasal degeneration (CBD), multiple system atrophy (MSA), and dementia with Lewy bodies (DLB) are the four major proteinopathic neurodegenerative disorders. Currently, there are no disease modifying therapies for these disorders. However, better understanding of the etiopathogenic mechanisms of these disorders has allowed the development of novel therapeutic approaches. These mainly include strategies directed to the pathologic conformational shift, seeding and aggregation, as well as transcellular spread of the proteins that aggregate in the brain which are α-synuclein and tau. Modulation of inflammatory responses and neuroprotection are also targets of interest. A number of clinical trials have been performed and others are ongoing or are planned to address the authentic need for disease modifying treatments. However, challenges exist in terms of accurate early clinical diagnostic criteria and robust outcome measures, and preclinical animal models that would best recapitulate human disease.